Filsafat Pengetahuan, Teologia, Mitologi dan Warna Kehidupan Lanjut Usia sebagai Umat Kristianidi HKBP Perumnas II Bekasi Selatan - Mesta Limbong; Manahan. P. Tampubolon; Gutser Siburian (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
The elderly is a normal process for every individual. The elderly are also not a burden on themselves or the internal/external environment. For this reason, regulations in Indonesia provide information that the number of elderly people is increasing nationally in Indonesia. The elderly at HKBP Perumnas II South Bekasi are part of the number of elderly in Indonesia. They have programmed activities, but they also need enlightenment from the scientific field and its implications as Christians. The aim of the seminar and discussion with topics related to the Philosophy of Knowledge, Theology, Mythology and the Color of Life for the Elderly as Christians at HKBP Perumnas II South Bekasi